Chronic small bowel obstruction in a patient with post-radiation enteropathy. Case report - Aleksandr V. Leontiev; Lilia K. Indejkina; Mikhail A. Danilov; Elena A. Sabelnikova; Mariia A. Orlyuk; Konstantin O. Abramov; Alina A. Makarova; Asfold I. Parfenov (Терапевтический архив)
Сase report of late radiation damage to the small intestine in a patient who underwent laparoscopic extirpation of uterine cancer and radiation therapy is presented. The article shows the clinical manifestations of chronic post-radiation enteritis with a long progressive course and the development of partial intestinal obstruction, demonstrating the importance of timely diagnosis and the implementation of a multidisciplinary approach in the treatment of patients with late radiation damage to the intestine.